Nematodiasis en ovinos de abasto en el camal municipal de Huánuco - Bazan Garcia, Augusto (2017)
In order to obtain an estimate of the nematosis sheep in the Huanuco region, took a nonrandom sample of sheep for slaughter from areas adjacent to the municipal slaughterhouse of Huanuco, considering the month, sex, age, type or breed of animal, season and gender of the parasite. The determination was made by examining parasites fecal samples subjected to sedimentation / flotation of Zn sulfate. The annual prevalence was 73.9%, being higher in the months of March to June and September to October, corresponding to the rainy season and lower during the months of July and August, when the season correponden summer. No significant differences between sexes or age. The number of parasite genera was higher in the month of September.